LncRNA TDRG1/miR‐214‐5p axis affects preeclampsia by modulating trophoblast cells. (29th December 2019) - Gong, Fengyan; Cheng, Huiyan; Shi, Yuee; Cui, Lifeng; Jia, Guifeng
Abstract : Because of limited treatment options, preeclampsia (PE) is the leading cause of perinatal morbidity and mortality worldwide. Recently, lncRNA TDRG1 is reported to be aberrantly down‐regulated in PE placenta, and the abnormal expression of TDRG1 might play a key or partial role in PE development. In this study, we found that TDRG1 was significantly down‐regulated in PE placenta compared with the normal placenta. The cell proliferation, migration, invasion, and cell cycle were explored by CCK‐8, wound‐healing, transwell, and flow cytometer assay, respectively. Experimental results showed that TDRG1 accelerated the proliferation, migration, and invasion of trophoblast cells. Dual‐luciferase reporter assays confirmed that TDRG1 could bind to miR‐214‐5p. Besides, knockdown of TDRG1 suppressed the cell proliferation, migration, and invasion, while knockdown of miR‐214‐5p reversed the effect. Jagged1 and Notch1 were negatively regulated by miR‐214‐5p while positively modulated by TDRG1. In conclusion, TDRG1 promoted trophoblast cells viability and invasion by negatively regulating miR‐214‐5p expression, contributing to a better understanding of PE pathogenesis and providing new light on TDRG1‐directed diagnosis and treatment. Significance of the study: In this work, we observed that TDRG1 was able to promote cell proliferation, migration, and invasion cells by suppressing the expression of miR‐214‐5p and regulating the Notch signalling pathway in trophoblast cells. As far as we know, the effect of TDRG1/miR‐214‐5p axis on cell viability, migration, and invasion of trophoblast cells was firstly introduced. Our findings provided a better understanding of the mechanism of PE. Moreover, it is reasonable to believe that TDRG1 may be employed as a strategy to treat PE in the future.